Weight-adjusted-waist index is associated with urinary albumin-creatinine ratio in normal body mass index adults: a cross-sectional study from NHANES 2001–2018 - Gao, Pengjie; Wang, Danni; Zhuo, Yan; Kamili, Kamila; Li, Xiyang; Xu, Suining; Tian, Gang (Scientific reports, 2025)
Obesity promotes chronic kidney disease and albuminuria. Whether weight-adjusted-waist index (WWI) is correlated with albuminuria reflected by urinary albumin-to-creatinine ratio (UACR) in normal body mass index (BMI) population and the effect of hypertension and hyperglycemia on the association remain unclear. This cross-sectional study included adults with complete WWI and UACR data in the National Health and Nutrition Examination Survey (NHANES) database from 2001 to 2018. WWI was defined as waist circumference (WC) divided by the square root of weight. Linear regression, restricted cubic splines (RCS) curve and logistic regression were performed to evaluate the relationship between WWI and albuminuria risk. The relationship in different blood pressure and glucose subgroups were further investigated. 10,105 participants were finally included. The prevalence of albuminuria was 5.05%. WWI in albuminuria group was higher. RCS curve analysis showed the relationship between WWI and albuminuria risk increased linearly in patients with hypertension or hyperglycemia, while a U-shaped curve relationship in normoglycemic or non-hypertensive individuals. Logistic regression results indicated increased WWI was an independent risk factor for albuminuria reflected by UACR in normal BMI population even after adjusting for confounding factors, especially in males. When patients only had hypertension with normal blood glucose, WWI was still independently associated with albuminuria. Elevated WWI increased albuminuria risk in normal BMI adults, especially in males and patients with hypertension or hyperglycemia, even in hypertension patients without hyperglycemia. Assessment of WWI to identify early renal dysfunction should be emphasized.